Gambaran Kedisiplinan Belajar Pada Siswa Kelas XI SMK Negeri 7 Semarang - Anggreni, Melliana Septi Dwi; Rakhmawati, Dini; Windaniati, Windaniati (Prodi Bimbingan dan Konseling Fakultas Keguruan dan Ilmu Pendidikan | Universitas Islam As-Syafi'iyah, 2024)
The purpose of this research is to determine the depiction of learning discipline among 11th-grade students at SMK Negeri 7 Semarang. This research uses a descriptive quantitative approach with a survey method. The population in this research comprises all 11th-grade students at SMK Negeri 7 Semarang, totaling 612 students. The sample taken in this study consists of 191 11th-grade students. The sampling technique used is random sampling. For data collection, a Likert scale of learning discipline is used, and data analysis is conducted using SPSS 23 and Excel. Based on the research results on the